Gemina - Kaufman, Amie; Kristoff, Jay; Lu, Marie, 1984- (2016)
"When the space station Heimdall is invaded, Hannah and Nik must work together to defeat the enemy"--
On board the Jump Station Heimdall, Hanna is the captain's pampered daughter; Nik a member of a notorious crime family. While they are struggling with the realities of life aboard the galaxy's most boring space station, little do they know that Kady Grant and the Hypatia are headed right toward Heimdall, carrying news of the Kerenza invasion. When an elite BeiTech strike team invades the station, Hanna and Nik are thrown together. But alien predators are picking off the station residents one by one, and a malfunction in the station's wormhole means the space-time continuum might be ripped in two. The fate of the Hypatia-- and possibly the known universe-- is in their hands.
Keywords: Science fiction; Space stations -- Fiction; Interplanetary voyages -- Fiction; Artificial intelligence -- Fiction; Space stations -- Fiction; Interplanetary voyages -- Fiction; Artificial intelligence -- Fiction; Science fiction; Science fiction